The design and evaluation of clinical decision support systems in the area of pharmacokinetics. - Hwang, Hsin-Ginn
Gentamicin, an antibiotic drug, can be used in one-sided (unilateral) Menier's disease to end frequent attacks of spontaneous disabling vertigo. However, with incorrect dose treatment it can profoundly damage patients' inner ear and kidney. The dosage of medication and the dosage interval will affect serum concentration that results therapeutic or damage. Pharmacokinetics is the study of managing the relationship between the dosage medication, dosing interval, and serum concentration. However, due to the complicated mathematical equations of pharmacokinetics, it is rarely used in clinics. The purpose of this study was to use a pharmacokinetics model to build a prototype of gentamicin CDSS embedded in a PDA. This system was implemented in a district teaching hospital in Chiayi area, Taiwan. Empirical data was collected under routine clinical setting with real patients and physicians to validate this CDSS. The research results showed that, considering the therapeutic effect, the pharmacokinetics-based CDSS outperforms physicians' experience. Regarding the intoxication, the pharmacokinetics-based CDSS also performed better than physicians' experience with less intoxication. The physicians using the system revealed a high degree of agreement with the perceived usefulness, perceived ease of use, and intention to use the pharmacokinetics-based CDSS.
Keywords: Clinical Decision Support System (CDSS).; Personal Digital Assistant (PDA).; One compartment model; Pharmacokinetics; First order kinetics